Negative active material and preparation method thereof, negative pole piece and secondary battery

By growing titanium dioxide nanowires in situ on porous micron silicon particles and coated with carbon cladding and carbon nanotubes, the structural damage caused by the size changes of micron silicon materials during the lithium ion deintercalation process is solved, and the circulation performance and energy density of the battery are improved.

CN119725500APending Publication Date: 2025-03-28REPT BATTERO ENERGY CO LTD
View PDF 0 Cites 2 Cited by

Patent Information

Application Number
CN202510020669.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-06
Publication Date
2025-03-28

AI Technical Summary

Technical Problem

In traditional lithium-ion batteries, micron silicon carbon materials are prone to dimensional changes during the lithium ion deintercalation process, resulting in structural damage and powdering, and reducing the cycling performance and volume energy density of the battery.

Method used

Porous micron silicon particles are used as cores, and titanium dioxide nanowires are grown in situ on their surface to form a carbon cladding layer of the shell and dispersed carbon nanotubes. The structural stability of the negative electrode active material is improved through the synergistic effect of these components.

Benefits of technology

It effectively suppresses the expansion and rupture of micron silicon particles during charging and discharging, improves the cycling and rate performance of the battery, and ensures the volume energy density of micron silicon materials.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119725500A_ABST
    Figure CN119725500A_ABST
Patent Text Reader

Abstract

The invention relates to a negative active material and a preparation method thereof, a negative pole piece and a secondary battery. The negative electrode active material comprises: a core part comprising porous micron silicon particles and titanium dioxide nanowires; the shell part is coated on at least part of the surface of the core part, and the shell part comprises a carbon coating layer and carbon nanotubes dispersed on the carbon coating layer; wherein one ends of at least part of the titanium dioxide nanowires are arranged on the hole walls of the porous silicon particles, and the other ends of at least part of the titanium dioxide nanowires extend out of the porous silicon particles. According to the negative electrode active material provided by the invention, through the synergistic effect among the porous structure of the porous micron silicon particles, the titanium dioxide nanowires, the carbon coating layer and the carbon nanotubes, the structural stability of the negative electrode active material is improved, the volume energy density of the micron silicon material is ensured to be exerted, and the cycle performance and the rate capability of the battery are improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of batteries, and in particular to a negative electrode active material and a preparation method thereof, a negative electrode sheet, and a secondary battery. Background Art

[0002] Lithium-ion batteries are widely used in consumer electronics, energy storage devices, electric vehicles, etc. due to their high energy density, long cycle life and low self-discharge rate. Among them, silicon-based negative electrode materials have great potential for improving energy density due to their excellent theoretical specific capacity (about 4200 mAh / g).

[0003] In traditional technology, nano-processing of silicon particles can effectively alleviate the stress caused by the huge volume expansion of silicon particles during charging and discharging, and improve the stability and cycle life of the electrode. However, nano-silicon has a large specific surface area and serious side reactions; the compaction density is low, making it difficult to achieve high energy density of the battery; and the preparation cost of nano-scale materials is high and the mixing of materials is difficult.

[0004] Compared with nano-silicon-carbon materials, micron-silicon-carbon materials have higher tap density and theoretical volume energy density, and lower production cost. However, their large-sized particles are prone to significant size changes during the lithium-ion insertion and extraction process, leading to structural damage and pulverization, which not only reduces the battery's cycle performance, but also makes electrical contact impossible at the cracks, reducing the actual volume energy density. Summary of the invention

[0005] Based on this, it is necessary to provide a negative electrode active material and its preparation method, a negative electrode plate, and a secondary battery to inhibit the dimensional change during ion insertion and extraction, reduce the damage and pulverization of particles, improve the structural stability of the negative electrode active material, and ensure the volume energy density of the micron silicon material.

[0006] The first aspect of the present application provides a negative electrode active material, which includes: a core portion, including porous micron silicon particles and titanium dioxide nanowires; a shell portion, coating at least a portion of the surface of the core portion, the shell portion including a carbon coating layer and carbon nanotubes dispersed in the carbon coating layer; wherein at least a portion of the titanium dioxide nanowires have one end disposed on a pore wall of the porous micron silicon particles, and the other end extending to the outside of the porous micron silicon particles.

[0007] In some embodiments, the average particle size D of the porous micron silicon particles is v 50 is 1μm~10μm.

[0008] In some embodiments, the average pore size of the porous micron silicon particles is 50 nm to 300 nm.

[0009] In some embodiments, the average diameter of the titanium dioxide nanowires is 10 nm to 100 nm.

[0010] In some embodiments, the average length of the titanium dioxide nanowires is 0.2 μm to 5 μm.

[0011] In some embodiments, the thickness of the carbon coating layer is 2 nm to 20 nm.

[0012] In some embodiments, the negative electrode active material has a sphericity of 0.85 to 0.96.

[0013] In some embodiments, the tensile strength of the negative electrode active material is 30 MPa to 50 MPa.

[0014] In some embodiments, the tap density of the negative electrode active material is 1.5 g / cm 3 ~1.8 g / cm 3 .

[0015] In some embodiments, the ionic conductivity of the negative electrode active material at 25°C is 5.0×10 -6 S / cm~8.0×10 -6 S / cm.

[0016] In some embodiments, the electronic conductivity of the negative electrode active material at 25°C is 2.0×10 -2 S / cm~5.0×10 -2 S / cm.

[0017] The second aspect of the present application provides a method for preparing a negative electrode active material, which comprises the following steps: in situ growing titanium dioxide nanowires on porous micron silicon particles to obtain a core portion; coating the surface of the core portion with a carbon coating layer dispersed with carbon nanotubes to form a shell portion to obtain a negative electrode active material.

[0018] In some embodiments, the step of in-situ growing titanium dioxide nanowires on the surface of porous micron silicon particles to obtain a core portion specifically includes the following steps: dispersing the porous micron silicon particles in a titanium dioxide precursor solution, adjusting the pH to acidic, performing a hydrothermal reaction, and drying to obtain a core portion; wherein the concentration of the titanium dioxide precursor solution is 0.01 mol / L~0.16 mol / L.

[0019] In some embodiments, the step of coating the surface of the core with a carbon coating layer dispersed with carbon nanotubes to form a shell to obtain a negative electrode active material specifically includes the following steps: mixing the core, the carbon source and the carbon nanotubes, and granulating them by spray drying to obtain a precursor; carbonizing the precursor, coating the surface of the core with a carbon coating layer dispersed with carbon nanotubes to form a shell to obtain a negative electrode active material.

[0020] The third aspect of the present application provides a negative electrode plate, which includes the negative electrode active material provided by the first aspect above, or the negative electrode active material prepared by the preparation method provided by the second aspect above.

[0021] A fourth aspect of the present application provides a secondary battery, which includes the negative electrode plate provided by the third aspect.

[0022] Compared with the traditional technology, this application has at least the following beneficial effects:

[0023] The negative electrode active material provided by the present application has a synergistic effect between the porous structure of the porous micron silicon particles, the titanium dioxide nanowires, the carbon coating layer and the carbon nanotubes. On the one hand, the porous structure of the porous micron silicon particles alleviates the expansion of the micron silicon particles to a certain extent, and the carbon coating layer protects the structure of the porous micron silicon particles and the titanium dioxide nanowires in the core. At the same time, the titanium dioxide material has good structural stability, and its crystal structure will not change due to the deintercalation of lithium ions during the charging and discharging process. It not only plays a role in buffering the expansion of the micron silicon particles, but also effectively protects the porous silicon structure, reduces the risk of micron silicon particles breaking and pulverizing, and improves the structural stability of the negative electrode active material, thereby improving the cycle performance of the battery. On the other hand, even if the carbon coating is destroyed during the process of lithium insertion and extraction and cracks appear on the surface of the micron silicon particles, at this time, since one end of the titanium dioxide nanowire is arranged on the pore wall of the porous micron silicon particle and the other end extends to the outside of the porous micron silicon particle, the titanium dioxide nanowire forms a continuous and uniform nano-network structure, thereby ensuring the electrical contact stability between the porous micron silicon particles and the current collector, reducing the problem of increased interface impedance during the cycle process, and ensuring the volume energy density of the micron silicon material; further, the excellent ionic conductivity of titanium dioxide is combined with the excellent electronic conductivity of carbon nanotubes to improve the rate performance of the battery.

[0024] In addition, titanium dioxide nanowires have high chemical stability, which can inhibit the occurrence of side reactions and optimize the formation quality of the interfacial SEI film, further improving the long-cycle stability and coulombic efficiency of the battery.

[0025] In summary, the negative electrode active material provided by the present application improves the structural stability of the negative electrode active material through the synergistic effect between the porous structure of porous micron silicon particles, titanium dioxide nanowires, carbon coating layers and carbon nanotubes, ensures the volume energy density of the micron silicon material, and improves the cycle performance and rate performance of the battery. BRIEF DESCRIPTION OF THE DRAWINGS

[0026] Figure 1 Schematic diagram of the structure of the negative electrode active material in one embodiment of the present application.

[0027] Figure 2Schematic diagram of a process for preparing a negative electrode active material in one embodiment of the present application.

[0028] 1. Negative electrode active material; 10. Core; 11. Porous micron silicon particles; 12. Titanium dioxide nanowires; 20. Shell; 21. Carbon coating layer; 22. Carbon nanotubes. DETAILED DESCRIPTION

[0029] References to embodiments of the present application will now be provided in detail, one or more examples of which are described below. Each example is provided as an explanation rather than a limitation of the present application. In fact, it will be apparent to those skilled in the art that various modifications and variations may be made to the present application without departing from the scope or spirit of the present application. For example, a feature described or described as part of one embodiment may be used in another embodiment to produce a further embodiment.

[0030] Therefore, it is intended that the present application covers such modifications and variations that fall within the scope of the appended claims and their equivalents. Other objects, features and aspects of the present application are disclosed in or are apparent from the following detailed description. It will be appreciated by those of ordinary skill in the art that this discussion is merely a description of exemplary embodiments and is not intended to limit the broader aspects of the present application.

[0031] In the present application, the technical features described in an open manner include closed technical solutions composed of the listed features, and also include open technical solutions containing the listed features.

[0032] In this application, when it comes to numerical ranges, unless otherwise specified, the above numerical ranges are deemed to be continuous and include the minimum and maximum values ​​of the range, as well as each value between such minimum and maximum values. Further, when a range refers to an integer, each integer between the minimum and maximum values ​​of the range is included. In addition, when multiple ranges are provided to describe features or characteristics, the ranges can be merged. In other words, unless otherwise specified, all ranges disclosed herein should be understood to include any and all subranges included therein.

[0033] Unless otherwise specified, all embodiments and optional embodiments of the present application can be combined with each other to form a new technical solution.

[0034] Unless otherwise specified, all technical features and optional technical features of this application can be combined with each other to form a new technical solution.

[0035] If there is no special explanation, all steps of the present application can be performed sequentially or randomly, preferably sequentially. For example, the method includes steps (a) and (b), which means that the method may include steps (a) and (b) performed sequentially, or may include steps (b) and (a) performed sequentially. For example, it is mentioned that the method may also include step (c), which means that step (c) can be added to the method in any order. For example, the method may include steps (a), (b) and (c), or may include steps (a), (c) and (b), or may include steps (c), (a) and (b), etc.

[0036] If there is no special explanation, the "include" and "comprising" mentioned in this application are open-ended or closed-ended. For example, the "include" and "comprising" may mean that other components not listed may also be included or only the listed components may be included or only the listed components may be included.

[0037] If not specifically stated, in this application, the term "or" is inclusive. For example, the phrase "A or B" means "A, B, or both A and B". More specifically, any of the following conditions satisfies the condition "A or B": A is true (or exists) and B is false (or does not exist); A is false (or does not exist) and B is true (or exists); or both A and B are true (or exist).

[0038] The first aspect of the present application provides a negative electrode active material 1, such as Figure 1 As shown, the negative electrode active material 1 includes a core 10 and a shell 20. The core 10 includes porous micron silicon particles 11 and titanium dioxide nanowires 12. The shell 20 is coated on at least part of the surface of the core 10, and the shell 20 includes a carbon coating layer 21 and carbon nanotubes 22 dispersed in the carbon coating layer 21. Among them, at least one end of the titanium dioxide nanowire 12 is arranged on the pore wall of the porous micron silicon particle 11, and the other end extends to the outside of the porous micron silicon particle 11.

[0039] The negative electrode active material 1 provided by the present application has a synergistic effect between the porous structure of the porous micron silicon particles 11, the titanium dioxide nanowires 12, the carbon coating layer 21 and the carbon nanotubes 22. On the one hand, the porous structure of the porous micron silicon particles 11 alleviates the expansion of the micron silicon particles to a certain extent, and the carbon coating layer 21 protects the structure of the porous micron silicon particles 11 and the titanium dioxide nanowires 12 in the core part 10. At the same time, the titanium dioxide material has good structural stability, and its crystal structure will not change due to the deintercalation of lithium ions during the charging and discharging process. It not only plays a role in buffering the expansion of the micron silicon particles, but also effectively protects the porous silicon structure, reduces the risk of rupture and pulverization of the micron silicon particles, and improves the structural stability of the negative electrode active material 1, thereby improving the cycle performance of the battery. On the other hand, even if the carbon coating layer 21 is destroyed during the process of lithium insertion and extraction, and cracks appear on the surface of the micron silicon particles, at this time, since one end of the titanium dioxide nanowire 12 is arranged on the pore wall of the porous micron silicon particle 11 and the other end extends to the outside of the porous micron silicon particle 11, the titanium dioxide nanowire 12 forms a continuous and uniform nano-network structure, thereby ensuring the electrical contact stability between the porous micron silicon particle 11 and the current collector, reducing the problem of increased interface impedance during the cycle process, and ensuring the volume energy density of the micron silicon material; further, the excellent ionic conductivity of titanium dioxide is combined with the excellent electronic conductivity of the carbon nanotube 22 to improve the rate performance of the battery.

[0040] In addition, titanium dioxide nanowires 12 have high chemical stability, can inhibit the occurrence of side reactions, optimize the formation quality of the interface SEI film, and further improve the long-cycle stability and coulombic efficiency of the battery.

[0041] In summary, the negative electrode active material 1 provided in the present application improves the structural stability of the negative electrode active material 1 through the synergistic effect between the porous structure of the porous micron silicon particles 11, the titanium dioxide nanowires 12, the carbon coating layer 21 and the carbon nanotubes 22, ensures the volume energy density of the micron silicon material, and improves the cycle performance and rate performance of the battery.

[0042] Herein, "porous micron silicon" refers to a silicon element having a micron-level structure with multiple pores. The porous micron silicon of the present application can be purchased from the market, or prepared by chemically etching micron silicon.

[0043] In some embodiments, a portion of the titanium dioxide nanowires 12 are disposed on the pore walls of the porous micron silicon particles 11 and extend to the outside of the porous micron silicon particles 11 , and another portion of the titanium dioxide nanowires 12 are disposed on the surface of the porous micron silicon particles 11 .

[0044] In some embodiments, the average particle size D of the porous micron silicon particles 11 is V50 is 1 μm to 10 μm. For example, the average particle size of the porous micron silicon particles 11 may be, but is not limited to, 1 μm, 2 μm, 3 μm, 4 μm, 5 μm, 6 μm, 7 μm, 8 μm, 9 μm, or 10 μm.

[0045] Herein, "average particle size" refers to the median particle size (D V 50), that is, the particle size at which the volume accumulation reaches 50% from the small particle size side in the volume-based particle size distribution.

[0046] In some embodiments, the average pore size of the porous micron silicon particles 11 is 50 nm to 300 nm. For example, the average pore size of the porous micron silicon particles 11 may be, but is not limited to, 50 nm, 75 nm, 100 nm, 125 nm, 150 nm, 175 nm, 200 nm, 225 nm, 250 nm, 275 nm, and 300 nm.

[0047] It can be understood that the present application adopts porous micron silicon particles 11 as the core of the negative electrode active material, which overcomes the serious side reaction problem caused by the high specific surface area of ​​nano silicon particles in traditional technology, reduces irreversible capacity loss, improves the first coulombic efficiency, and reduces the decomposition loss of the electrolyte; the micron silicon particles are not easy to agglomerate during the slurry preparation process, and the material has better dispersion, which is conducive to the uniform coating of the slurry and improves the processing performance of the electrode; the porous structure of the porous micron silicon particles 11 provides an effective buffer space, which can accommodate the volume expansion of silicon during the charging and discharging process, reduces stress concentration, improves the mechanical strength of the material, reduces the risk of particle cracking, and improves the cycle life of the battery; the micron silicon particles have higher packing density and tap density, which greatly improves the volume energy density of the battery.

[0048] The performance of the porous micron silicon particles 11 combined with the titanium dioxide nanowires 12 grown on the pore walls and the carbon coating layer 21 with carbon nanotubes 22 improves the electrochemical performance and structural stability of the negative electrode active material 1, thereby improving the energy density and cycle performance of the battery.

[0049] Herein, the "average pore size" is measured by a nitrogen isothermal adsorption-desorption method.

[0050] In some embodiments, the average diameter of the titanium dioxide nanowires 12 is 10 nm to 100 nm. For example, the average diameter of the titanium dioxide 12 can be, but is not limited to, 10 nm, 15 nm, 20 nm, 25 nm, 30 nm, 35 nm, 40 nm, 45 nm, 50 nm, 55 nm, 60 nm, 65 nm, 70 nm, 75 nm, 80 nm, 85 nm, 90 nm, 95 nm, and 100 nm.

[0051] In some embodiments, the average length of the titanium dioxide nanowires 12 is 0.2 μm to 5 μm. For example, the average length of the titanium dioxide nanowires 12 can be, but is not limited to, 0.2 μm, 0.4 μm, 0.6 μm, 0.8 μm, 1 μm, 1.2 μm, 1.4 μm, 1.6 μm, 1.8 μm, 2 μm, 2.2 μm, 2.4 μm, 2.6 μm, 2.8 μm, 3 μm, 3.2 μm, 3.4 μm, 3.6 μm, 3.8 μm, 4 μm, 4.2 μm, 4.4 μm, 4.6 μm, 4.8 μm, and 5 μm.

[0052] It can be understood that the high aspect ratio of titanium dioxide nanowires provides a fast ion transport channel, thereby increasing the ion migration rate of the negative electrode active material, helping to reduce polarization and improve rate performance.

[0053] In some embodiments, the thickness of the carbon coating layer 21 is 2 nm to 20 nm. For example, the thickness of the carbon coating layer 21 may be, but is not limited to, 2 nm, 3 nm, 4 nm, 5 nm, 6 nm, 7 nm, 8 nm, 9 nm, 10 nm, 12 nm, 14 nm, 16 nm, 18 nm, and 20 nm.

[0054] In some embodiments, the sphericity of the negative electrode active material 1 is 0.85 to 0.96. Exemplarily, the sphericity of the negative electrode active material 1 may be, but is not limited to, 0.85, 0.86, 0.87, 0.88, 0.89, 0.9, 0.91, 0.92, 0.93, 0.94, 0.95, 0.96. Within the above range, the particles of the negative electrode active material 1 have a higher sphericity, thereby improving the compression strength and formability of the particles of the negative electrode active material 1, further improving the tap density of the negative electrode active material 1, facilitating the use of energy density, and improving processability.

[0055] It is worth noting that since the negative electrode active material 1 provided in the present application is at the micron level, based on its large size characteristics, the high sphericity will not cause the negative electrode active material 1 particles to agglomerate and deactivate; however, if nano-silicon is used, due to its small size, when the sphericity is high, agglomeration and deactivation of the negative electrode active material particles are likely to occur.

[0056] Herein, "sphericity" refers to the ratio of the shortest diameter to the longest diameter of the particles of the negative electrode active material 1 .

[0057] In some embodiments, the tensile strength of the negative electrode active material 1 is 35 MPa to 50 MPa. For example, the tensile strength of the negative electrode active material 1 may be, but is not limited to, 35 MPa, 36 MPa, 38 MPa, 40 MPa, 42 MPa, 44 MPa, 46 MPa, 48 MPa, or 50 MPa.

[0058] Herein, "tensile strength" refers to the stress of a material when it is subjected to the maximum tensile force in a tensile test, which is measured by a tensile testing machine.

[0059] In some embodiments, the tap density of the negative electrode active material 1 is 1.5 g / cm 3 ~1.8 g / cm 3 For example, the tap density of the negative electrode active material 1 may be, but is not limited to, 1.5 g / cm 3 , 1.6 g / cm 3 , 1.7 g / cm 3 , 1.8 g / cm 3 .

[0060] In this article, “tapped density” refers to the mass per unit volume of the powder in a container after being tapped under specified conditions, and the unit is g / cm 3 , usually measured using a special tap density instrument. Since the volume of the battery is limited, the higher the tap density, the more active materials are contained per unit volume, so the battery has a higher energy density.

[0061] In some embodiments, the ionic conductivity of the negative electrode active material 1 at 25° C. is 5×10 -6 S / cm~8×10 -6 S / cm. For example, the ionic conductivity of the negative electrode active material 1 at 25°C may be, but is not limited to, 5×10 -6 S / cm, 5.5×10 -6 S / cm, 6×10 -6 S / cm, 6.5×10 -6 S / cm, 7×10 -6 S / cm, 7.5×10 -6 S / cm, 8×10 -6 S / cm.

[0062] In some embodiments, the electronic conductivity of the negative electrode active material 1 at 25°C is 2×10 -2 ~5×10 -2 S / cm. For example, the electronic conductivity of the negative electrode active material 1 at 25°C may be, but is not limited to, 2×10 -2 S / cm, 2.5×10-2 S / cm, 3×10 -2 S / cm, 3.5×10 -2 S / cm, 4×10 -2 S / cm, 4.5×10 -2 S / cm, 5×10 -2 S / cm.

[0063] The second aspect of the present application provides a method for preparing a negative electrode active material, such as Figure 2 As shown, the preparation method comprises the following steps:

[0064] S1. In-situ growth of titanium dioxide nanowires on porous micron silicon particles to obtain a core.

[0065] S2. The surface of the core is coated with a carbon coating layer in which carbon nanotubes are dispersed to form a shell, thereby obtaining a negative electrode active material.

[0066] The preparation method provided by the present application is to grow titanium dioxide nanowires in situ on porous micron silicon particles to obtain a structure in which at least one end of the titanium dioxide nanowires is arranged on the pore wall of the porous silicon particles and the other end extends to the outside of the porous silicon particles. Therefore, even if the carbon coating layer is destroyed during the process of lithium extraction and cracks appear on the surface of the micron silicon particles, the titanium dioxide nanowires can still maintain the electrical connection of the material, thereby ensuring the volume energy density of the micron silicon material. The carbon coating layer with carbon nanotubes dispersed on the surface of the core part protects the structure of the porous micron silicon particles and titanium dioxide nanowires in the core part, reduces the risk of micron silicon particles breaking and pulverizing, improves the structural stability of the negative electrode active material, and thus improves the cycle performance of the battery.

[0067] Herein, "in situ growth" refers to the growth of titanium dioxide nanowires on the surface and pore walls of porous micron-sized silicon particles; this application does not limit the method of in situ growth of titanium dioxide, and hydrothermal growth method, sol-gel method, etc. can all be used to in situ grow titanium dioxide nanowires on porous micron-sized silicon particles.

[0068] In some implementation modes, step S1 specifically includes the following steps:

[0069] S11, dispersing porous micron silicon particles in a titanium dioxide precursor solution, adjusting the pH to acidic, drying, and performing a hydrothermal reaction to obtain a core portion.

[0070] Among them, the concentration of the titanium dioxide precursor solution is 0.01 mol / L~0.16 mol / L.

[0071] Illustratively, the concentration of the titanium dioxide precursor solution can be, but is not limited to, 0.01 mol / L, 0.02 mol / L, 0.03 mol / L, 0.04 mol / L, 0.05 mol / L, 0.06 mol / L, 0.07 mol / L, 0.08 mol / L, 0.09 mol / L, 0.10 mol / L, 0.11 mol / L, 0.12 mol / L, 0.13 mol / L, 0.14 mol / L, 0.15 mol / L, or 0.16 mol / L.

[0072] In some embodiments, the titanium dioxide precursor in the titanium dioxide precursor solution includes at least one of titanium tetrachloride, tetrabutyl titanate, and tetraisopropyl titanate.

[0073] In some other embodiments, step S1 specifically includes the following steps: immersing the porous micron silicon particles in a titanium dioxide precursor sol, and then sequentially performing gelation treatment and calcination treatment to obtain a core portion.

[0074] In some of the embodiments, the specific conditions of the gelation treatment are: drying the titanium dioxide precursor sol at 100° C. to 120° C.

[0075] In some of the embodiments, the specific conditions of the calcination treatment are: temperature of 300° C. to 600° C., and time of 1 h to 3 h.

[0076] In some implementation modes, step S2 specifically includes the following steps:

[0077] S21, after mixing the core part, the carbon source and the carbon nanotubes, granulating them by spray drying to obtain a precursor.

[0078] S22, carbonizing the precursor, coating the surface of the core with a carbon coating layer in which carbon nanotubes are dispersed, forming a shell, and obtaining a negative electrode active material.

[0079] The negative electrode active material particles obtained by spray drying have a higher sphericity, thereby improving the compression strength and formability of the negative electrode active material particles, further improving the tap density of the negative electrode active material, which is beneficial to the energy density and improves the processability.

[0080] In some embodiments, in step S21, the carbon source includes at least one of glucose, sucrose, cyclodextrin, starch, cellulose, polyvinyl alcohol and phenolic resin; preferably, the carbon source is starch.

[0081] In some of the embodiments, in step S21, the inlet air temperature of the spray drying method is 150°C~250°C, the outlet air temperature is 70°C~100°C, the spray pressure is 0.8 MPa~1.2 MPa, and the feed rate is 3 mL / min~10 mL / min.

[0082] In some embodiments, in step S21, the water content of the precursor particles formed by spray drying granulation is ≤5%.

[0083] In some embodiments, in step S22, the temperature of the carbonization treatment is 800° C. to 1000° C., and the time is 1 h to 3 h.

[0084] The third aspect of the present application provides a negative electrode plate, which includes the negative electrode active material provided by the first aspect above, or the negative electrode active material prepared by the preparation method provided by the second aspect above.

[0085] Generally speaking, the negative electrode plate includes a negative electrode current collector and a negative electrode active material layer. The negative electrode active material layer is arranged on at least one side of the negative electrode current collector. The negative electrode active material layer includes the negative electrode active material provided by the first aspect above, or the negative electrode active material prepared by the preparation method provided by the second aspect above.

[0086] In some embodiments, the negative electrode current collector may be a metal foil or a composite current collector. For example, as the metal foil, a copper foil may be used. The composite current collector may include a polymer material base layer and a metal layer formed on at least one surface of the polymer material substrate. The composite current collector may be formed by forming a metal material (copper, copper alloy, nickel, nickel alloy, titanium, titanium alloy, silver and silver alloy, etc.) on a polymer material substrate (such as a substrate of polypropylene (PP), polyethylene terephthalate (PET), polybutylene terephthalate (PBT), polystyrene (PS), polyethylene (PE), etc.).

[0087] In some embodiments, the negative electrode active material layer may further include a binder. The binder may include at least one of styrene-butadiene rubber (SBR), polyacrylic acid (PAA), sodium polyacrylate (PAAS), polyacrylamide (PAM), polyvinyl alcohol (PVA), sodium alginate (SA), polymethacrylic acid (PMAA), or carboxymethyl chitosan (CMCS).

[0088] In some embodiments, the negative electrode active material layer may further include a conductive agent, which may include at least one of superconducting carbon, acetylene black, carbon black, Ketjen black, carbon dots, carbon nanotubes, graphene, or carbon nanofibers.

[0089] In some of the embodiments, the negative electrode active material layer may further include other additives, such as a thickener (eg, sodium carboxymethyl cellulose (CMC-Na)).

[0090] In some embodiments, the negative electrode active material layer may further include other negative electrode active materials. For example, the other negative electrode active materials include carbon materials. The carbon materials include at least one of graphite, soft carbon, and hard carbon.

[0091] A fourth aspect of the present application provides a secondary battery, which includes the negative electrode plate provided by the third aspect.

[0092] In some embodiments, the secondary battery includes a lithium ion battery or a sodium ion battery. The secondary battery of the present application includes a battery cell form, a battery module form and a battery pack form.

[0093] Generally, a secondary battery includes a positive electrode sheet, a negative electrode sheet, an electrolyte and a separator. During the charge and discharge process of a secondary battery, active ions are embedded and removed back and forth between the positive electrode sheet and the negative electrode sheet. The electrolyte plays the role of conducting ions between the positive electrode sheet and the negative electrode sheet. The separator is set between the positive electrode sheet and the negative electrode sheet, mainly to prevent the positive and negative electrodes from short-circuiting, while allowing ions to pass through.

[0094] In some embodiments, the positive electrode sheet includes a positive electrode current collector and a positive electrode active material layer, the positive electrode active material layer is disposed on at least one side of the positive electrode current collector, and the positive electrode active material layer includes a positive electrode active material.

[0095] As an example, the positive electrode current collector has two surfaces facing each other in its thickness direction, and the positive electrode active material layer is disposed on any one or both of the two facing surfaces of the positive electrode current collector.

[0096] In some embodiments, the positive electrode current collector may be a metal foil or a composite current collector. For example, aluminum foil may be used as the metal foil. The composite current collector may include a polymer material base and a metal layer formed on at least one surface of the polymer material base. The composite current collector may be formed by forming a metal material (aluminum, aluminum alloy, nickel, nickel alloy, titanium, titanium alloy, silver and silver alloy, etc.) on a polymer material substrate (such as a substrate of polypropylene (PP), polyethylene terephthalate (PET), polybutylene terephthalate (PBT), polystyrene (PS), polyethylene (PE), etc.).

[0097] In some embodiments, the positive electrode active material layer may further include a positive electrode active material. The positive electrode active material may be a positive electrode active material for a battery known in the art.

[0098] As an example, when the positive electrode plate is used in a lithium-ion battery, the positive electrode active material may adopt a positive electrode active material for lithium-ion batteries known in the art. Furthermore, the positive electrode active material may include at least one of the following materials: lithium-containing phosphates with an olivine structure, lithium transition metal oxides, and their respective modified compounds. However, the present application is not limited to these materials, and other traditional materials that can be used as positive electrode active materials for batteries may also be used. These positive electrode active materials may be used alone or in combination of two or more. Among them, examples of lithium transition metal oxides may include, but are not limited to, lithium cobalt oxide (such as LiCoO2), lithium nickel oxide (such as LiNiO2), lithium manganese oxide (such as LiMnO2, LiMn2O4), lithium nickel cobalt oxide, lithium manganese cobalt oxide, lithium nickel manganese oxide, lithium nickel cobalt manganese oxide (such as LiNi 1 / 3 Co 1 / 3 Mn 1 / 3 O2 (also referred to as NCM333), LiNi 0.5 Co 0.2 Mn 0.3 O2 (also referred to as NCM523), LiNi 0.5 Co 0.25 Mn 0.25 O2 (also referred to as NCM211), LiNi 0.6 Co 0.2 Mn 0.2 O2 (also referred to as NCM622), LiNi 0.8 Co 0.1 Mn 0.1 O2 (also referred to as NCM811), lithium nickel cobalt aluminum oxide (such as LiNi 0.8 Co 0.15 Al 0.05 O2) or at least one of its modified compounds, etc. Examples of lithium-containing phosphates with an olivine structure may include, but are not limited to, at least one of lithium iron phosphate (such as LiFePO4 (also referred to as LFP)), a composite material of lithium iron phosphate and carbon, lithium manganese phosphate (such as LiMnPO4), a composite material of lithium manganese phosphate and carbon, lithium iron manganese phosphate, and a composite material of lithium iron manganese phosphate and carbon.

[0099] In some embodiments, the positive electrode active material layer may further include a binder. As an example, the binder may include at least one of polyvinylidene fluoride (PVDF), polytetrafluoroethylene (PTFE), vinylidene fluoride-tetrafluoroethylene-propylene terpolymer, vinylidene fluoride-hexafluoropropylene-tetrafluoroethylene terpolymer, tetrafluoroethylene-hexafluoropropylene copolymer, and fluorine-containing acrylate resin.

[0100] In some of the embodiments, based on the total mass of the positive electrode active material layer, the mass proportion of the binder is 0.5% to 3%, for example, 0.5%, 1%, 1.5%, 2%, 2.5%, 3%, etc.

[0101] In some embodiments, the positive electrode active material layer may further include a conductive agent. As an example, the conductive agent may include at least one of superconducting carbon, acetylene black, carbon black, Ketjen black, carbon dots, carbon nanotubes, graphene, and carbon nanofibers.

[0102] In some of the embodiments, based on the total mass of the positive electrode active material layer, the mass proportion of the conductive agent is 0.8% to 4%, for example, 0.8%, 1%, 1.5%, 2%, 2.5%, 3%, 3.5%, 4%, etc.

[0103] In some of the embodiments, the positive electrode sheet can be prepared in the following manner: the components for preparing the positive electrode sheet, such as the positive electrode active material, the conductive agent, the binder and any other components are dispersed in a solvent (such as N-methylpyrrolidone) to form a positive electrode slurry; the positive electrode slurry is coated on the positive electrode collector, and after drying, cold pressing and other processes, the positive electrode sheet can be obtained.

[0104] The present application has no specific restrictions on the type of electrolyte, which can be selected according to needs. For example, the electrolyte can be liquid, gel or all-solid.

[0105] In some embodiments, the electrolyte is an electrolyte solution, which includes an electrolyte salt and a solvent.

[0106] In some of the embodiments, when the secondary battery is a lithium ion battery, the electrolyte salt may include at least one of lithium hexafluorophosphate, lithium tetrafluoroborate, lithium perchlorate, lithium hexafluoroarsenate, lithium bisfluorosulfonyl imide, lithium bistrifluoromethanesulfonyl imide, lithium trifluoromethanesulfonate, lithium difluorophosphate, lithium difluorooxalatoborate, lithium dioxalatoborate, lithium difluorodioxalatophosphate, and lithium tetrafluorooxalatophosphate.

[0107] In some embodiments, the solvent may include at least one of ethylene carbonate, propylene carbonate, ethyl methyl carbonate, diethyl carbonate, dimethyl carbonate, dipropyl carbonate, methyl propyl carbonate, ethyl propyl carbonate, butylene carbonate, fluoroethylene carbonate, methyl formate, methyl acetate, ethyl acetate, propyl acetate, methyl propionate, ethyl propionate, propyl propionate, methyl butyrate, ethyl butyrate, 1,4-butyrolactone, cyclopentane, dimethyl sulfone, ethylene glycol dimethyl ether, methyl ethyl sulfone and diethyl sulfone.

[0108] In some embodiments, the electrolyte may further include additives, such as negative electrode film-forming additives, positive electrode film-forming additives, and additives that can improve certain battery properties, such as additives that improve battery overcharge performance, additives that improve battery high or low temperature performance, etc.

[0109] The present application has no particular limitation on the type of isolation membrane, and any known porous isolation membrane with good chemical stability and mechanical stability can be selected.

[0110] In some embodiments, the material of the isolation membrane may include at least one of glass fiber, non-woven fabric, polyethylene, polypropylene or polyvinylidene fluoride. The isolation membrane may be a single-layer film or a multi-layer composite film, without particular limitation. When the isolation membrane is a multi-layer composite film, the materials of each layer may be the same or different, without particular limitation.

[0111] In some embodiments, the positive electrode sheet, the negative electrode sheet and the separator can be formed into an electrode assembly by a winding process or a lamination process.

[0112] In some embodiments, the battery cell may include an outer packaging, which may be used to encapsulate the electrode assembly and the electrolyte.

[0113] In some embodiments, the outer packaging of the battery cell may be a hard shell, such as a hard plastic shell, an aluminum shell, a steel shell, etc. The outer packaging of the battery cell may also be a soft package, such as a bag-type soft package. The material of the soft package may be plastic, and the plastic may be polypropylene, polybutylene terephthalate, polybutylene succinate, etc.

[0114] The secondary battery provided in the present application can be used as a power source for an electrical device, or as an energy storage unit for an electrical device. Electrical devices may include mobile devices, electric vehicles, electric trains, ships and satellites, energy storage systems, etc., but are not limited thereto. Among them, mobile devices may be, for example, mobile phones, laptop computers, etc.; electric vehicles may be, for example, pure electric vehicles, hybrid electric vehicles, plug-in hybrid electric vehicles, electric bicycles, electric scooters, electric golf carts, electric trucks, etc., but are not limited thereto.

[0115] The present application will be further described below with reference to specific embodiments and comparative examples.

[0116] Example 1

[0117] This embodiment provides a negative electrode active material. The negative electrode active material is prepared by the following steps:

[0118] Step 1: Preparation of porous micron silicon

[0119] Weigh 0.2 g of silver nitrate and dissolve it in 50 mL of deionized water to prepare a silver ion solution; add 5 g of micron silicon particles to the above silver ion solution and stir for 10 minutes to ensure sufficient mixing; slowly add 5 mL of 5% hydrofluoric acid solution and continue stirring the reaction at 25°C for 4 hours; after the reaction is completed, wash the silicon particles with deionized water several times until neutral, and then dry the sample in a vacuum drying oven at 60°C for 12 hours to obtain porous micron silicon particles.

[0120] The concentration of the silver ion solution is 4 g / L; the average particle size of the porous micron silicon is D v 50 is 5μm, and the average pore size of porous micron silicon is 300nm.

[0121] Step 2: Preparation of the core

[0122] 1.36g of tetrabutyl titanate, a titanium dioxide precursor, was dissolved in 50mL of ethanol to obtain a 0.08mol / L titanium dioxide precursor solution; 1g of porous micron silicon powder was dispersed in the titanium dioxide precursor solution; 50mL of deionized water was taken, 0.5mL of 1M hydrochloric acid was added, and stirred evenly to obtain an acid-containing deionized water solution; then the acid-containing deionized water solution was slowly added dropwise to the titanium dioxide precursor solution, the pH value was adjusted to acidic, and the reaction was stirred at 50°C for 2 hours; the above solution was transferred to a 100mL hydrothermal reactor, and the reaction was carried out at 180°C for 10 hours to promote the in-situ growth of titanium dioxide nanowires on the porous micron silicon; after the reaction was completed, the product was centrifuged and washed with ethanol and deionized water for multiple times, and then vacuum dried at 80°C for 12 hours to obtain the core.

[0123] The average diameter of the titanium dioxide nanowires is 50 nm and the average length is 0.5 μm.

[0124] Step 3: Preparation of negative electrode active material

[0125] 1) 1 g of the core, 0.2 g of carbon nanotubes and 0.8 g of starch were added to 50 mL of deionized water, ultrasonically dispersed for 30 min, and then granulated by a spray dryer; after drying, spherical particles were collected and further dried in a vacuum drying oven at 60 ° C for 4 hours to obtain a precursor.

[0126] The inlet air temperature of the spray drying was set to 160°C, the outlet air temperature was set to 80°C, the spray pressure was 1.2 MPa, and the feed rate was 5 mL / min.

[0127] 2) The precursor is carbonized at a temperature of 900° C. for 2 hours to coat the surface of the core with a carbon coating layer having dispersed carbon nanotubes to form a shell, thereby obtaining a negative electrode active material.

[0128] The thickness of the carbon coating layer is 10 nm.

[0129] Example 2

[0130] The preparation method of the negative electrode active material provided in this embodiment is basically the same as that in embodiment 1, except that:

[0131] In step S1, 0.1 g of silver nitrate was weighed and dissolved in 50 mL of deionized water to prepare a silver ion solution; the concentration of the silver ion solution was 2 g / L. The average pore size of the prepared porous micron silicon was 50 nm.

[0132] Example 3

[0133] The preparation method of the negative electrode active material provided in this embodiment is basically the same as that in embodiment 1, except that:

[0134] In step S1, 0.4 g of silver nitrate was weighed and dissolved in 50 mL of deionized water to prepare a silver ion solution; the concentration of the silver ion solution was 8 g / L. The average pore size of the prepared porous micron silicon was 200 nm.

[0135] Example 4

[0136] The preparation method of the negative electrode active material provided in this embodiment is basically the same as that in embodiment 1, except that:

[0137] In step S2, 0.17 g of tetrabutyl titanate, a titanium dioxide precursor, was dissolved in 50 mL of ethanol to obtain a 0.01 mol / L titanium dioxide precursor solution.

[0138] Among them, the average diameter of titanium dioxide nanowires is 10nm and the average length is 0.2μm.

[0139] Example 5

[0140] The preparation method of the negative electrode active material provided in this embodiment is basically the same as that in embodiment 1, except that:

[0141] In step S2, 2.72 g of tetrabutyl titanate, a titanium dioxide precursor, was dissolved in 50 mL of ethanol to obtain a 0.16 mol / L titanium dioxide precursor solution.

[0142] The average diameter of the titanium dioxide nanowires is 100 nm and the average length is 5 μm.

[0143] Example 6

[0144] The preparation method of the negative electrode active material provided in this embodiment is basically the same as that in embodiment 1, except that:

[0145] In step S3, the mass of the carbon nanotubes is 0.1 g, and the mass of the starch is 0.5 g.

[0146] Wherein, the thickness of the carbon coating layer is 2 nm.

[0147] Example 7

[0148] The preparation method of the negative electrode active material provided in this embodiment is basically the same as that in embodiment 1, except that:

[0149] In step S3, the mass of the carbon nanotubes is 0.5 g, and the mass of the starch is 1.2 g.

[0150] Wherein, the thickness of the carbon coating layer is 20 nm.

[0151] Example 8

[0152] The preparation method of the negative electrode active material provided in this embodiment is basically the same as that in embodiment 1, except that:

[0153] Step 3: Preparation of negative electrode active material

[0154] 1) 1 g of the core, 0.2 g of carbon nanotubes and 0.8 g of starch were added to 50 mL of deionized water, ultrasonically dispersed for 30 min, and dried by rotary evaporation to obtain a precursor;

[0155] 2) The precursor is carbonized at a temperature of 900° C. for 2 hours to coat the surface of the core with a carbon coating layer having dispersed carbon nanotubes to form a shell, thereby obtaining a negative electrode active material.

[0156] Wherein, the thickness of the carbon coating layer is 8nm.

[0157] Comparative Example 1

[0158] Negative electrode active material: micron silicon particles (average particle size D v 50 is 5μm).

[0159] Comparative Example 2

[0160] Negative electrode active material:

[0161] Step 1: Preparation of the core

[0162] 1.36 g of titanium dioxide precursor tetrabutyl titanate was dissolved in 50 mL of ethanol to obtain a 0.08 mol / L titanium dioxide precursor solution; 1 g of micron silicon powder (average particle size D v50 is 5μm) dispersed in the titanium dioxide precursor solution; take another 50mL deionized water, add 0.5mL 1M hydrochloric acid, stir evenly to obtain an acid-containing deionized water solution; then slowly add the acid-containing deionized water solution to the titanium dioxide precursor solution, adjust the pH value to acidic, and stir the reaction at 50℃ for 2 hours; transfer the above solution to a 100mL hydrothermal reactor, react at 180℃ for 10 hours to promote the growth of titanium dioxide nanowires on the surface of micron silicon particles; after the reaction is completed, the product is centrifuged and washed with ethanol and deionized water for multiple times, and then vacuum dried at 80℃ for 12 hours to obtain the core.

[0163] The average diameter of the titanium dioxide nanowires is 80 nm and the average length is 0.5 μm.

[0164] Step 2: Preparation of negative electrode active materials

[0165] 1) 1 g of the core, 0.2 g of carbon nanotubes and 0.8 g of starch were added to 50 mL of deionized water, ultrasonically dispersed for 30 min, and then granulated by a spray dryer; after drying, spherical particles were collected and further dried in a vacuum drying oven at 60 ° C for 4 hours to obtain a precursor.

[0166] The inlet air temperature of the spray drying was set to 160°C, the outlet air temperature was set to 80°C, the spray pressure was 1.2 bar, and the feed rate was 5 mL / min.

[0167] 2) The precursor is carbonized at a temperature of 900° C. for 2 hours to coat the surface of the core with a carbon coating layer having dispersed carbon nanotubes to form a shell, thereby obtaining a negative electrode active material.

[0168] The thickness of the carbon coating layer is 10 nm.

[0169] Comparative Example 3

[0170] The negative electrode active material provided in this comparative example is substantially the same as that in Example 1, except that:

[0171] Replace the micron silicon particles in step 1 with nano silicon particles (average particle size D v 50 is 200nm).

[0172] Performance Testing

[0173] 1. Negative electrode active material testing

[0174] (1) Sphericity test

[0175] The morphology of the negative electrode active material particles in the above embodiments and comparative examples was observed using a scanning electron microscope (SEM) (model: JEOL JSM-7600F, manufacturer: JEOL Ltd.), and the sphericity of the negative electrode active material particles was measured using image analysis software.

[0176] The specific test method is as follows: Place the sample on the SEM sample stage, fix it and then evacuate it. Set the acceleration voltage to 5kV and obtain the morphology of the sample surface. Use image processing software such as ImageJ to measure the particle outline and calculate the sphericity. The test results are shown in Table 1.

[0177] (2) Material compressive strength test

[0178] A micro compression tester (model: Instron 5943, manufacturer: Instron) was used to place a single particle of the negative electrode active material in the above embodiments and comparative examples in the fixture of the compression tester, and a vertical pressure was applied to the particle at a speed of 0.5 mm / min. The maximum pressure value when the particle broke was recorded, which was the compressive strength. The test results are shown in Table 1.

[0179] (3) Tap density test

[0180] First, weigh 50 g of the negative electrode active material powder of the above-mentioned embodiments and comparative examples as a sample, then pour the sample into a measuring cylinder, take care to avoid violent vibration, gently scrape the surface of the powder with a ruler to record the initial volume V1; fix the measuring cylinder on a tap density meter, vibrate the sample with a fixed amplitude of 3 mm and a vibration number of 1000 times, and record the final volume V2 of the powder after compaction.

[0181] Tap density = mass of negative electrode active material powder / final volume V2 of powder after tapping.

[0182] (4) Ionic conductivity test

[0183] The negative electrode sheet obtained by drying and coating with a slurry of negative electrode active material: binder PVDF: conductive agent carbon black = 8:1:1 is used to form a symmetrical button electrode with two lithium metal sheets. The negative electrode sheet is between the two lithium sheets, and the electrolyte is 1 mol / L LiPF6 dissolved in a mixed solution of EC:DMC=1:1 (volume ratio).

[0184] The battery was placed in a constant temperature environmental box and connected to an electrochemical workstation (model: Autolab PGSTAT302N, manufacturer: Metrohm Autolab). The temperature was controlled at 25°C ± 2°C and allowed to stand for at least 30 minutes before testing to ensure uniform heat distribution.

[0185] Test frequency range: 0.1 Hz-1 MHz;

[0186] Excitation signal: voltage amplitude 5 mV-10 mV (avoid nonlinearity);

[0187] Then obtain the Nyquist diagram: Extract the ion migration related parameter resistance R according to the impedance characteristic curve b , the resistance of the negative electrode active material is obtained by equivalent circuit fitting, and the ionic conductivity is calculated:

[0188] ;

[0189] in:

[0190] t: sample thickness (cm);

[0191] A: sample cross-sectional area (cm²);

[0192] R b : Bulk resistance (Ω) determined from the Nyquist plot in the high-frequency region.

[0193] The test results are shown in Table 1.

[0194] (5) Electronic conductivity test

[0195] The electronic conductivity of the negative electrode active materials in the above embodiments and comparative examples was measured using a four-probe test system (model: Keithley 2450 Sourcemeter, manufacturer: Keithley Instruments).

[0196] The specific test steps are as follows: Press the material into a sheet and connect it to the test system using a four-probe fixture. Set the current to 1μA and measure the voltage drop on the sample. Calculate the electronic conductivity of the sample based on the current, voltage and probe spacing. The test results are shown in Table 1.

[0197] Table 1

[0198]

[0199] As shown in Table 1, by comparing Examples 1 to 8 and Comparative Examples 1 to 3, it can be seen that the negative electrode active material provided in the present application has the characteristics of high sphericity, high compressive strength, high tap density, high ionic conductivity and high electronic conductivity, thereby improving the structural stability, mechanical properties, processability and conductivity of the negative electrode active material, which is beneficial to the performance of the capacity of the negative electrode active material.

[0200] 2. Battery test

[0201] The negative electrode active materials in the above examples and comparative examples were prepared into CR2032 button batteries, and the batteries were placed in a battery test system. Cyclic charge and discharge tests were performed on the batteries at room temperature at a rate of 0.5C. The first discharge capacity and the 500th discharge capacity were recorded. Capacity retention rate = (500th discharge capacity / 1st discharge capacity) × 100%. The test results are shown in Table 2.

[0202] Table 2

[0203]

[0204] As shown in Table 2, by comparing Examples 1 to 8 and Comparative Examples 1 to 3, it can be seen that when the negative electrode active material provided by the present application is applied to a battery, it is beneficial to exert the energy density of the micron silicon material and improve the capacity retention rate of the battery.

[0205] The technical features of the above-described embodiments may be arbitrarily combined. To make the description concise, not all possible combinations of the technical features in the above-described embodiments are described. However, as long as there is no contradiction in the combination of these technical features, they should be considered to be within the scope of this specification.

[0206] The above-described embodiments only express several implementation methods of the present application, and the descriptions thereof are relatively specific and detailed, but they cannot be understood as limiting the scope of the present application. It should be pointed out that, for a person of ordinary skill in the art, several modifications and improvements can be made without departing from the technical concept of the present application, and these all belong to the protection scope of the present application. Therefore, the protection scope of the present application shall be subject to the attached claims.

Claims

1. A negative electrode active material, characterized in that: include: The core part includes porous micron silicon particles and titanium dioxide nanowires; A shell portion, covering at least a portion of the surface of the core portion, wherein the shell portion includes a carbon coating layer and carbon nanotubes dispersed in the carbon coating layer; Wherein, at least one end of a portion of the titanium dioxide nanowires is disposed on the pore wall of the porous micron silicon particle, and the other end extends to the outside of the porous micron silicon particle.

2. The negative electrode active material according to claim 1, characterized in that The average particle size D of the porous micron silicon particles v 50 is 1 μm to 10 μm; and / or, The average pore size of the porous micron silicon particles is 50nm-300nm.

3. The negative electrode active material according to claim 1, characterized in that The average diameter of the titanium dioxide nanowires is 10 nm to 100 nm; and / or, The average length of the titanium dioxide nanowires is 0.2 μm to 5 μm.

4. The negative electrode active material according to claim 1, characterized in that The thickness of the carbon coating layer is 2nm~20nm.

5. The negative electrode active material according to any one of claims 1 to 4, characterized in that: The negative electrode active material satisfies at least one of the following conditions: (1) The sphericity of the negative electrode active material is 0.85 to 0.96; (2) The tensile strength of the negative electrode active material is 35 MPa to 50 MPa; (3) The tap density of the negative electrode active material is 1.5 g / cm 3 ~1.8 g / cm 3 ; (4) The ionic conductivity of the negative electrode active material at 25°C is 5.0×10 -6 S / cm~8.0×10 -6 S / cm; (5) The electronic conductivity of the negative electrode active material at 25°C is 2.0×10 -2 S / cm~5.0×10 -2 S / cm.

6. A method for preparing a negative electrode active material, characterized in that: The following steps are involved: In-situ growth of titanium dioxide nanowires on porous micron silicon particles to obtain a core; The surface of the core portion is coated with a carbon coating layer in which carbon nanotubes are dispersed to form a shell portion, thereby obtaining a negative electrode active material.

7. The method for preparing the negative electrode active material according to claim 6, characterized in that: The step of in-situ growing titanium dioxide nanowires on the surface of porous micron silicon particles to obtain a core portion specifically comprises the following steps: The porous micron silicon particles are dispersed in a titanium dioxide precursor solution, the pH is adjusted to acidic, a hydrothermal reaction is performed, and the solution is dried to obtain a core portion; Wherein, the concentration of the titanium dioxide precursor solution is 0.01 mol / L~0.16 mol / L.

8. The method for preparing the negative electrode active material according to claim 6, characterized in that: The step of coating the surface of the core with a carbon coating layer in which carbon nanotubes are dispersed to form a shell to obtain a negative electrode active material specifically comprises the following steps: After mixing the core, the carbon source and the carbon nanotubes, granulation is performed by spray drying to obtain a precursor; The precursor is carbonized to coat the surface of the core with a carbon coating layer in which carbon nanotubes are dispersed to form a shell, thereby obtaining a negative electrode active material.

9. A negative electrode plate, characterized in that: The invention comprises the negative electrode active material according to any one of claims 1 to 5, or the negative electrode active material prepared by the preparation method according to any one of claims 6 to 8.

10. A secondary battery, characterized in that: Comprising the negative electrode sheet as claimed in claim 9.

Citation Information

Cited By

  • Negative pole piece, solid-state battery and electric device

    CN120709351A

  • Negative electrode sheet, solid-state battery, electric device

    CN120709351B